Continuous respiratory support in quadriplegic children by bilateral phrenic nerve stimulation. Issue 8 (August 1987) - Garrido, H; Mazaira, J; Gutierrez, P; Gonzalez, E; Rivas, J; Madrazo, J
Abstract : Three children, aged 6-10 years, in whom cervical cord injury at the C1-C2 level resulted in apnoea had bilateral implantation of diaphragm pacemakers. With periods of gradual conditioning of the diaphragm muscle to low frequency stimulation and slow respiratory rates they adapted to continuous ventilatory support by simultaneous stimulation of both hemidiaphragms without evidence of fatigue, so far for periods of 23-47 months.